COVID-19 preparedness and response in rural and remote areas: A scoping review. - Lilian Dudley; Ian Couper; Niluka Wijekoon Kannangarage; Selvan Naidoo; Clara Rodriguez Ribas; Theadora Swift Koller; Taryn Young (Public Library of Science (PLoS), 2023)
This scoping review used the Arksey and O'Malley approach to explore COVID-19 preparedness and response in rural and remote areas to identify lessons to inform future health preparedness and response planning. A search of scientific and grey literature for rural COVID-19 preparedness and responses identified 5 668 articles published between 2019 and early 2022. A total of 293 articles were included, of which 160 (54.5%) were from high income countries and 106 (36.2%) from middle income countries. Studies focused mostly on the Maintenance of Essential Health Services (63; 21.5%), Surveillance, epidemiological investigation, contact tracing and adjustment of public health and social measures (60; 20.5%), Coordination and Planning (32; 10.9%); Case Management (30; 10.2%), Social Determinants of Health (29; 10%) and Risk Communication (22; 7.5%). Rural health systems were less prepared and national COVID-19 responses were often not adequately tailored to rural areas. Promising COVID-19 responses involved local leaders and communities, were collaborative and multisectoral, and engaged local cultures. Non-pharmaceutical interventions were applied less, support for access to water and sanitation at scale was weak, and more targeted approaches to the isolation of cases and quarantine of contacts were preferable to blanket lockdowns. Rural pharmacists, community health workers and agricultural extension workers assisted in overcoming shortages of health professionals. Vaccination coverage was hindered by weaker rural health systems. Digital technology enabled better coordination, communication, and access to health services, yet for some was inaccessible. Rural livelihoods and food security were affected through disruptions to local labour markets, farm produce markets and input supply chains. Important lessons include the need for rural proofing national health preparedness and response and optimizing synergies between top-down planning with localised planning and coordination. Equity-oriented rural health systems strengthening and action on rural social determinants is essential to better prepare for and respond to future outbreaks.